Prevalence, molecular epidemiology and intra-hospital acquisition of Klebsiella pneumoniae strains producing carbapenemases in an Italian teaching hospital from January 2015 to September 2016. (June 2017) - Bartolini, Andrea; Basso, Monica; Franchin, Elisa; Menegotto, Nicola; Ferrari, Anna; De Canale, Ettore; Andreis, Samantha; Scaggiante, Renzo; Stefani, Stefania; Palù, Giorgio; Parisi, Saverio Giuseppe
Highlights: Most of the positive surveillance rectal swabs (SRS) had a previous negative SRS. Twelve Klebsiella pneumoniae strains harboured more than one carbapenemase gene. Many other species harbouring a carbapenemase gene were collected. Abstract: Objectives: We described Klebsiella pneumoniae producing carbapenemase (CPKP) spread from 01/01/2015 to 13/09/16 in a tertiary level hospital. Methods: The first positive surveillance rectal swab (SRS) or clinical sample (CS) collected in the medical department (MD), surgical department (SD) and intensive care department (ICD) were included in the study. A validated in-house Real-Time PCR method was used to detect carbapenemases; multilocus sequence typing (MLST) was used for further characterization of the strains. Results: 21535 patients were included: 213 CPKP strains from surveillance rectal swab (SRS) and 98 from clinical samples (CS) were collected. The percentage of CPKP detected in SRS with respect to CS increased in the medical MD from 2015 to 2016 (p = 0.01) and in ICD from 2012 to 2015 (p = 0.0001), while it decreased in SD from 2014 to 2016 (p = 0.003); 68.5% of the positive SRS had a previous negative SRS; CPKP was more frequently identified in CS than in SRS in MD. Twelve strains harboured more than one carbapenemase gene. Many other species harbouring a carbapenemase gene were collected. Conclusions: MDs need more inclusive surveillance criteria. The late detection of positive SRS underlined the risk of colonization during hospitalization.